LANDSCAPE DESIGN OF CONNECTIVITY ROUTES FOR THE TOD (TRANSIT ORIENTED DEVELOPMENT) BLOK M AREA SOUTH JAKARTA - Djasmin Ramadhanty, Bunga
The increasing population of the city of Jakarta has an impact on the increasing use of private vehicles for daily mobility activities. This problem is the foundation for the government to build public transportation modes to increase the interest of city residents so they don't depend on private vehicles. One of these ideas, the government is to develop the MRT (Mass Rapid Transit) mass transportation mode as an alternative solution to congestion, but the development of the area around transit also needs to be developed to support transit activities from one mode of public transportation to another. The DKI Jakarta government is building 13 MRT station points in phase 1 and 5 in the TOD area. One of these areas is the Blok M area. The Blok M area is a transit area that has a wide variety of functions, activities and mobilization activities that are quite high. There is still a lack of interest in walking in the Blok M transit area, influenced by the low level of connectivity and walkability. The lack of good facilities for pedestrians such as street furniture that is not well maintained, the lack of shade on pedestrian paths, the lack of transit plaza facilities for stopping or resting, the location of crossings that are far and unsafe result in a path not being connected. The area is planned to be carried out in the TOD Blok M core area with an area of approximately 64 ha and the detailed design development area is carried out in certain areas such as typical connectivity route corridors and transit plazas. This study aims to improve connectivity by creating a landscape, which is in a pedestrian space to provide an open green space as a transit plaza that can accommodate mobilization needs. By increasing the circulation of planned paths and supporting facilities safely and comfortably, this thesis is expected to produce an interconnection between activities in the Blok M TOD area so that people are more interested in walking due to the accommodation needs and convenience for pedestrians. Based on the results of observation and comparative analysis between the TOD Blok M – Sisingamangaraja City Design Guidelines and the existing conditions, an analysis of the physical conditions from the walkability aspect and an analysis of the ecological conditions that are devoted to aspects of connectivity development were also carried out to determine design interventions in infrastructure development and design details on the connectivity path the TOD Blok M area is in accordance with the City Design Guidelines which will be aligned with the walkability criteria along with other supporting elements, an alternative design is obtained to accommodate connectivity needs such as pelican crossing, level crossing, skywalk, easement and transit plaza. The space can improve connectivity between functions within the area with each space being standardized by walkability indicators which include safety and comfort. In area design, pedestrian walkways are made in accordance with city design guidelines and conveniences such as the existence of a green line that can function as a stormwater path to absorb, drain rainwater towards shelters and as a space to hide shade trees. Areas with narrow pedestrian paths where it is not possible to make green lanes on the side of the road will be planted with shade trees on the road body which is equipped with tree grids for tree maintenance needs and user convenience. Complete and well-maintained street furniture such as benches, trash cans and street lights are placed in accordance with the standard placement of street furniture that has been installed and adjusted to the needs of each area segment. As for making it easier for users to mobilize, several areas are designed by making signage as landmarks of an area so that pedestrians can more easily recognize a place as well as providing wayfinding in the Blok M TOD area placed at area intersections or connected to bus stops, stations or shelters to navigate pedestrians properly.